The uniqueness of the pedagogical experience in organizing mobile games for elementary school students - Raxmonov Azamat Ruzvonovich (Genius Journals, 2023)
In this article, the peculiarity of the pedagogical experience and the need to use methods and methods in organizing mobile games for elementary school students were discussed.
Keywords: sport; physical education; physical training; dynamic games